A Long-duration Superflare on the K Giant HD 251108 - Hans Moritz Günther; Dheeraj Pasham; Alexander Binks; Stefan Czesla; Teruaki Enoto; Michael Fausnaugh; Franz-Josef Hambsch; Shun Inoue; Hiroyuki Maehara; Yuta Notsu; Jan Robrade; J. H. M. M. Schmitt; et al. (The Astrophysical Journal)
Many giant stars are magnetically active, which causes rotational variability, chromospheric emission lines, and X-ray emission. Large outbursts in these emission features can set limits on the magnetic field strength and thus constrain the mechanism of the underlying dynamo. HD 251108 is a Li-rich active K-type giant. We find a rotational period of 21.3 days with color changes and additional long-term photometric variability. Both can be explained with very stable stellar spots. We followed the decay phase of a superflare for 28 days with NICER and from the ground. We track the flare decay in unprecedented detail in several coronal temperature components. With a peak flux around 10 ^34 erg s ^−1 (0.5–4.0 keV) and an exponential decay time of 2.2 days in the early decay phase, this is one of the strongest flares ever observed, yet it follows trends established from samples of smaller flares, for example, for the relations between H α and X-ray flux, indicating that the physical process that powers the flare emission is consistent over a large range of flare energies. We estimate a flare loop length about 2–4 times the stellar radius. No evidence is seen for abundance changes during the flare.